2019
DOI: 10.1558/jmbs.v1i2.11788
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Plural from Variable Input

Abstract: Natural languages frequently display both consistent and variable morphological patterns. Previous studies have indicated that variable morphological patterns are mastered more slowly than consistent ones. In particular, it has been argued that Chilean children, who are exposed to variable plural-marking, take longer to consistently associate the plural marker to a more-than-one interpretation than children who are exposed to non-variable plural-marking (e.g. children from Mexico City). Building on this previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Thus far, comprehension studies of natural language support the latter view, that is, children's reliance on only one form rather than two in language production is mirrored by their comprehension of one form, but not the other (e.g., Davies et al, 2019;Miller, 2014). For example, Miller and Schmitt (2012) found that children acquiring varieties of Spanish where /-s/ is variably omitted took longer to associate plural /-s/ to a more-than-one interpretation in comprehension as compared to children acquiring dialects of Spanish in which the plural marker is more consistently produced (see also Lukyanenko & Miller, 2019;Miller, 2007Miller, , 2014. Similarly, children acquiring African American English tend not only to omit third person singular -s (e.g., Newkirk-Turner & Green, 2016), but also do not comprehend it (De Villiers & Johnson, 2007).…”
Section: Production Vs Comprehensionmentioning
confidence: 99%
“…Thus far, comprehension studies of natural language support the latter view, that is, children's reliance on only one form rather than two in language production is mirrored by their comprehension of one form, but not the other (e.g., Davies et al, 2019;Miller, 2014). For example, Miller and Schmitt (2012) found that children acquiring varieties of Spanish where /-s/ is variably omitted took longer to associate plural /-s/ to a more-than-one interpretation in comprehension as compared to children acquiring dialects of Spanish in which the plural marker is more consistently produced (see also Lukyanenko & Miller, 2019;Miller, 2007Miller, , 2014. Similarly, children acquiring African American English tend not only to omit third person singular -s (e.g., Newkirk-Turner & Green, 2016), but also do not comprehend it (De Villiers & Johnson, 2007).…”
Section: Production Vs Comprehensionmentioning
confidence: 99%